The Hittites - Discoveries and Ongoing Research - Bryce, Trevor (History compass, 2004)
This article focuses on discoveries and advances in Hittite scholarship and archaeology over the past few decades, as the result of ongoing excavations in the Hittite capital and in regional centres of the kingdom. Of particular significance is the information provided by recent text finds, including that contained in clay tablets, seal impressions and monumental inscriptions on stone.